Calcium chloride effect on the quality of the cape gooseberry fruit (Physalis peruviana L.) - Pinzón-Sandoval, Elberth Hernando; Reyes, Andrea Johana; Álvarez-Herrera, Javier Giovanni (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The cape gooseberry is one of the promising crops in areas of high tropics, due to the nutritional characteristics presented by this fruit; however, this fruit is affected by disorders of physiological type, among these the fruit cracking, which can cause up to 30 % of post—harvest losses. This cracking can occur for many reasons, the most important among them are the fruit calcium deficiency, due to its low mobility via phloem, and the xylem/phloem ratio decrease in this fruit type. This paper objective was to evaluate the effect of calcium chloride (CaCl2) applied to both the fruit and the calyx preharvest, in doses of 1 % and 2 % (w/v). The polar and equatorial diameter, firmness, total soluble solid, total titratable acidity and color index were measured. Statistical differences were found (P$0.05) in all the variables, except firmness. The results indicate that the CaCl2 application, regardless of gender dose blockade the fruit ripening, possibly due to increased calcium in the fruit, which decreased respiratory activity and ethylene production, necessary to trigger starch processes hydrolysis, degradation of chlorophylls, enzyme activity and degradation of organic acids as fruit ripening’ own processes and thus, its organoleptic quality.